Estimates for Weighted K-Functionals Using the Least Concave Majorant of Weighted Moduli of Continuity. (2nd December 2017) - Păltănea, Radu; Talpău Dimitriu, Maria
ABSTRACT: We estimate the K -functional using the least concave majorant of modulus ω φ, where φ is a weight function on interval [ a, b ].